2006
DOI: 10.1785/0120040138
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Scattering of Elastic Waves by Subsurface Fractures and Cavities

Abstract: Comprehensive studies in geophysics and seismology have dealt with scattering phenomena in unbounded elastic domains containing fractures or cavities. Other studies have been carried out to investigate scattering by discontinuities located near a free surface. In this last case, the presence of fractures and cavities significantly affects wave motion and, in some cases, large resonant peaks may appear. To study these resonant peaks and describe how they can be affected by the presence of other near-free-surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 35 publications
4
28
0
1
Order By: Relevance
“…However, ½I∕2 þ A −1 does not exist if the frequency ω is an eigenfrequency of the interior problem with a rigid boundary condition on S (Martin, 2006;Rodriguez-Castellanos et al, 2006). In the eigenstate, there are nonzero eigenfunctions v k s that satisfy the following equation:…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ½I∕2 þ A −1 does not exist if the frequency ω is an eigenfrequency of the interior problem with a rigid boundary condition on S (Martin, 2006;Rodriguez-Castellanos et al, 2006). In the eigenstate, there are nonzero eigenfunctions v k s that satisfy the following equation:…”
Section: Theory and Methodsmentioning
confidence: 99%
“…When the imaginary part of the frequency is small (i.e., slow decay), the integral operator can still be close to singular. Another solution is the multiregion concept proposed by Rodriguez-Castellanos et al (2006), which splits an inclusion into three regions with overlapping boundaries extending to infinity. However, this technique may not be numerically straightforward when dealing with multiple cavities.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the physical effort related to the hammer work and source re-location, the stack adopted for each singleoffset is then often small and, consequently, the signal-to-noise ratio risks to be poor. This can be significant in some cases, especially for the radial Figure 4 Concise representation of the Full Velocity Spectrum (FVS) analysis: a phase velocity spectrum of a field dataset; b phase velocity spectrum of the synthetic model identified by means of the FVS optimization procedure presented in Dal Moro et al ( , 2016 and Dal Moro (2014); c compact representation of the two previous velocity spectra (the background colors represent the velocity spectrum of the field data, while the overlaying black contour lines pertain to the synthetic data); d same data as in the previous plot but from a different (3D) perspective component, which is often more sensitive to heterogeneities between the source and the receivers (e.g., Rodríguez-Castellanos et al 2006). …”
Section: Acquisition Of Multi-offset Multi-component Data (Mo-rpm-hs mentioning
confidence: 99%
“…In fact, data always and necessarily contain some noise (both coherent and incoherent) that can reflect differently on the considered components and objective functions. Rodríguez-Castellanos et al (2006) showed for instance that, with respect to the vertical component, the radial component of Rayleigh waves is more affected by possible cracks in the medium.…”
Section: Vol 175 (2018) Improved Holistic Analysis Of Rayleigh Wavementioning
confidence: 99%
“…Kattis et al (2003) used the BEM to study the harmonic body waves scattering by lined and unlined tunnels in an infinite poroelastic saturated soil. Rodriguez-Castellanos et al (2006) studied the scattering of P and SV waves by cracks and underground cavities using the indirect boundary element method (IBEM). Esmaeili et al (2006) analyzed the dynamic response of plane harmonic waves by a lined circular tunnel using the hybrid boundary and FEM.…”
Section: Introductionmentioning
confidence: 99%